Homer Lea : American soldier of fortune - Kaplan, Lawrence M. (Lawrence Martin), 1954- (American warriors (Lexington, Ky.), 2010)
As a five-feet-three-inch hunchback who weighed about 100 pounds, Homer Lea (1876-1912), was an unlikely candidate for life on the battlefield, yet he became a world-renowned military hero. In the Dragon's Lair: The Exploits of Homer Lea paints a revealing portrait of a diminutive yet determined man who never earned his valor on the field of battle, but left an indelible mark on his times.